A Multidimensional Analysis of Pilgrimage: Social, Economic, and Religious Authority in the Mbah Priok Grave Pilgrimage - Siti Khotijah; Farida Novita Rahmah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This article aims to examine the pilgrimage to Mbah Priok’s grave from social, economic, and religious perspectives. This qualitative research employs a combination of literature review, historical analysis, and anthropological methods. The study reveals that the Tomb of Mbah Priok, also known as Habib Hasan Al Hadad, serves as a significant pilgrimage site despite historical controversies. The Al Hadad family has maintained religious authority and withstood temporal challenges. Notably, in April 2010, the Al Hadad family engaged in a physical and administrative conflict with a company expanding the area. During Governor Ahok’s tenure, the tomb was designated a religious tourism site and cultural heritage, fostering economic growth for local businesses and the surrounding community. This research contributes to understanding the socio-economic and religious dynamics of pilgrimage sites, highlighting the complex interplay between tradition and modernity